The Effect of Work Discipline and Work Motivation on the Performance of Abab Subdistrict Office Employees, PALI Regency - Suci Ulan Dari (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to examine the effect of work discipline and work motivation on the performance of the Abab District Office employees. The data used in this study came from questionnaires, interviews, and a literature study. A multiple linear regression analysis methods is applied in this research. The results prove that work discipline has a significant positive effect on employee performance. Motivation is also proven to have a significant positive effect on employee performance. The results of this study are expected to help companies improve employee performance through discipline and work motivation